ASSESSMENT OF ADIPONECTIN, TRIGLYCERIDE, AND CHOLESTEROL LEVELS AMONG ELDERLY RESIDENTS OF NNEWI, ANAMBRA STATE, NIGERIA (Journal of Biomedical Investigation, 2024)
Background: The WHO defines aging as beginning at 65 years or older, highlighting the need to understand the interplay between adiponectin, triglycerides, and cholesterol in promoting elderly health. Critical to metabolic and cardiovascular well-being, these biomarkers interact complexly, serving as indicators and potential targets for improving overall health in aging populations.Aim: This research aims to evaluate the levels of adiponectin, triglycerides, and cholesterol among elderly residents of Nnewi, Anambra State, Nigeria, to better understand their metabolic and cardiovascular health status.Methods: This study evaluated serum levels of adiponectin, triglycerides, cholesterol, and BMI in 90 participants, including 45 elderly subjects (65 years and above) and 45 younger controls. Spectrophotometric methods were used for biomarker analysis, with statistical assessments conducted using t-tests and correlation analysis.Results: There were no significant differences in the mean serum levels of adiponectin, triglycerides, and cholesterol between the test and control groups (p = 0.38, 0.88, and 0.25, respectively; p > 0.05). However, the test group exhibited significantly higher mean values for BMI, SBP, and DBP (25.87 ± 5.03, 140.22 ± 22.41, and 87.78 ± 17.31, respectively; p < 0.05) compared to the control group. Correlation analysis revealed a weak positive correlation between triglycerides (TG) and waist circumference (WC) (r = 0.298, p = 0.047), as well as between cholesterol (CHOL) and diastolic blood pressure (DBP) (r = 0.326, p = 0.029) in the test group.Conclusion: These findings highlight the interplay between metabolic and cardiovascular factors, suggesting that elevated BMI and blood pressure may be linked to subtle changes in lipid metabolism and its relationship with anthropometric measures in the test group.
Keywords: Aging; Metabolic health; Adiponectin; Triglycerides; Cholesterol